Effect of film-forming regulation of the self-formed compound layer on the oxidation inhibition capacity of HfB2-SiC coating. Issue 15 (1st August 2022) - Wu, Binbin; Wang, Peipei; Ren, Xuanru; Zhang, Mingcheng; Chen, Yuexing; Kan, Tengfei; Shi, Dalin; Kang, Xueqin; Feng, Peizhong
Abstract: To heighten the oxidation inhibition capacity of HfB2 -SiC coating, film-forming regulation of the self-formed compound layer was utilized to enhance the dynamic stability and the oxygen hindering capacity of the coating. The oxidation process of the HfB2 -SiC coating in air from room temperature to 1700 °C can be divided into the lower temperature oxidation zone, the medium temperature protection zone and the high temperature corrosion zone. The oxidation activity of the coatings was significantly weakened in the medium temperature oxidation protection zone from 1100 °C to 1400 °C, which was selected as the film-forming regulation temperature region to ensure the lower film-forming wastage of the coatings. When the film-forming temperature was 1200 °C, the coating was uniformly covered by the glass layer with fewer defects. The values of active factor and inerting factor of the HfB2 -SiC coating after film-forming at 1200 °C were 0.151 and 0.953 × 10 −6  g cm −2  s −1, respectively, which show the lowest film-forming wastage of the coating. With further ascending the film-forming temperature, a large number of pores and cracks generated on the glass layer owing to the evaporation and release of the gaseous byproducts, which destroyed the structure of the glass layer and aggravated the oxidation wastage of the coating. With increasing the film-forming time at 1200 °C for 360 min, the protection efficiency of the HfB2 -SiC coating increased to 99.13%, the oxygen permeability and carbon loss rate decreased by 79.6% and 67.8%, respectively, which slowed down the oxidation activity and improved the dynamic stability of the coating during oxidation.